Ureaplasma urealyticum infection following organ transplantation: a case report and narrative review - Hongru Zhang; Liping Yang (Renal Failure)
Objective One case of Ureaplasma urealyticum (UU) infection after kidney transplantation was reported, and relevant literature was collected to provide a scientific reference basis for clinical diagnosis and treatment.Methods A case of UU infection after renal transplantation in our hospital was analyzed retrospectively. PubMed, Embase and Cochrane databases were searched for case reports of UU infection after organ transplantation before 30 June 2024. The clinical and laboratory characteristics, treatment and prognosis of UU infection were summarized and analyzed.Results A 65-year-old man underwent renal transplantation on 26 January 2022 due to chronic renal disease (grade 2) caused by focal sclerosing glomerulonephritis. Hyperammonaemia and coma occurred after the operation, and the patient died. A total of 38 case reports or series of cases were included in this study, involving 44 patients. The case reports included 22 cases of kidney transplantation, 11 cases of lung transplantation, 4 cases of heart transplantation,1 case of liver transplantation and 6 cases of multiple organ transplantation. Ureaplasma urealyticum infection occurred in 74.47% of cases within 1 month after transplantation, and the main symptoms after the infection were mental. After the onset of the disease, the most abnormal examination index was the increase of blood ammonia, followed by the increase of white blood cells. Therapeutic drugs included tetracyclines (doxycycline or minocycline), quinolones and azithromycin. The clinical symptoms could be significantly improved after 24 h of taking the fastest-acting medication. The highest mortality rate was in patients infected with Ureaplasma after lung transplantation.Conclusion Early identification of UU and timely and correct drug treatment are essential to saving the lives of patients.